Research on the method of virtual machine deployment in cloud computing - Xiao-yan ZHANG; Min-ne WANG; Xiao-feng DU (Tongxin xuebao)
A method of virtual machine deployment was proposed. The main purpose of the method was to reduce the resource fragments on the host. The method predicted the increment of the virtual machines of different specifications in the next period of time, and dynamically programmed the available CPU and memory of the host in the resources pool by the prediction. The method took into account the users' behaviors, pre-determined the resources allocation rules, when users applied a virtual machine, the virtual machine would be assigned to the specific host directly. In the end, the method was implemented on the CloudStack platform.The experiment demonstrates that the method can reduce the resource fragments effectively.